2022
DOI: 10.1007/698_2022_928
|View full text |Cite|
|
Sign up to set email alerts
|

Agricultural Land Degradation in the Czech Republic

Abstract: Soil degradation has been identified as a major threat to the productivity of agricultural land. In the Czech Republic, soils are threatened primarily by water and wind erosion, but compaction, loss of organic matter, loss of soil structure stability, pollution and over-fertilization, loss of biodiversity, and soil sealing are also major concerns. Poor soil health results in many off-site effects such as surface water siltation, groundwater pollution, loss of biodiversity in the countryside, and decreasing cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Due to the demand for various quarry products, quarry operations such as blasting and grinding are carried out to meet this demand, often without considering the implications of these activities on the comfort and well-being of the surrounding neighbourhood. 39 - 41 Consequently, this situation can lead to the abandonment of the area at times. 15 , 42 The findings of this study resonate with the works of Adetiloye and Nenuwa, 43 , 44 who observed similar negative impacts on residents in Ikere-Ekiti, Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the demand for various quarry products, quarry operations such as blasting and grinding are carried out to meet this demand, often without considering the implications of these activities on the comfort and well-being of the surrounding neighbourhood. 39 - 41 Consequently, this situation can lead to the abandonment of the area at times. 15 , 42 The findings of this study resonate with the works of Adetiloye and Nenuwa, 43 , 44 who observed similar negative impacts on residents in Ikere-Ekiti, Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of response of wheat to the applied fertilizers is significantly influenced by the soil type at the site [ 80 , 81 ]. Cambisols are the most abundant soils in the Czech Republic [ 82 ] and are considered to be naturally less fertile than Chernozems. The lower fertility of Cambisols is evident in the significant increase in the cultivated crop yield when externally supplied with mineral N. In naturally fertile Chernozems, the differences in wheat yield between N treatments may be less pronounced [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%